Child trafficking and religion: a case study of Almajiri education in Northern Nigeria - Garba, Umaru Kwagyang; Nik Mahmod, Nik Ahmad Kamal (International Journal of Business, Economics and Law, 2015)
Children are trafficked in Nigeria for various purposes which include prostitution, begging, hawking, rituals, etc and this has been on the raise, thereby posing a great challenge to the Nigeria Government despite numerous efforts put in place to fight the menace. The feature of Nigerian children as young as 5 to 12 years is threatened by this monster called child trafficking. Although, poverty, greed, corruption, peer pressure have been traditionally identified as factors responsible for child trafficking in Nigeria, manipulation of religion through “Almajiri” ( traditional way of acquiring Islamic knowledge) have also been identified as factor playing very significant role in child trafficking in Northern Nigeria which has 90 percent of its population as Muslims. The paper adopted doctrinal methodology where it analysed the relevant literature in the area both primary and secondary. The focus of this study is to examine the manipulation of religion through Almajiri education for child trafficking in Northern Nigeria and its consequence on the child. There is scarce of information on Almajiri system of education as a form of child trafficking in Northern Nigeria, but through an examination of the historical antecedents of Almajiri education, the study discovers that although the concept was meant to prepare a Muslim child to become a useful adult in the society, the practice have been abused over the years. The finding of the paper reveals that there is no law put in place which controls the practice of Almajiri Education in Northern Nigeria and therefore recommend that Nigeria Government should regulate the activities of these Islamic teachers by enacting a law that controls such practices.